Motivation and Problems of Memorizing Al-Qur'an - Manuela Sironi; Fusi Rachele; Shuxiang Anindya (Yayasan Adra Karima Hubbi, 2023)
Memorizers of the Qur'an often have problems in memorizing the Qur'an. The obstacles experienced were different. Age also affects the constraints experienced by memorizers of the Qur'an. Memorizers of the Koran at an early age have problems reading the Koran and cannot read the Koran. Every obstacle experienced by the memorizer of the Kalam Allah has a different solution depending on the state of the memorizer. The purpose of this study is to find solutions and answers to the difficulties experienced by memorizing the Qur'an. With the solution of this problem, it is hoped that it can help memorizers of the Qur'an to memorize more quickly and mutqin. The method used in this study is the Descriptive Qualitative method, in this study it describes ways and tips to make the process of memorizing the Qur'an easier. The results of the research are expected to be applied in memorizing and understanding the contents of the Qur'an. In this study, different methods were found for each memorizer depending on the situation and conditions of the memorizer.